GELIAT MONITORING DAN EVALUASI: PERSEDIAAN BENIH PADI - Suhayati, Ely; Sarifudin, Dedi; Melinda, Bella (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
Raw material inventory stands as the largest asset within a company's holdings. However, discrepancies arise within the rice seed inventory, diverging from government accounting standards, alongside instances of double recording of income from rice seed sales. This research aims to address these issues. Employing a descriptive research method, the study focuses on work units at Subang The Large Testing Center For Standard Rice Instruments, with 4 respondents: the Warehouse Section, Administration Section, Inventory Operator, and Receipt Treasurer. Findings reveal that the The Large Testing Center For Standard Rice Instruments categorizes seed supplies as raw material, when they should be classified as animal and plant supplies, intended for sale or distribution to the public. Moreover, the rationale behind the double recording of self-produced rice seed supplies lacks presentation at production cost. Consequently, it is advised to record inventory in process and reclassify it within the inventory of animals/plants designated for sale or distribution to the public, and necessary monitoring and evaluation of the socialization of the Circular Letter of the Secretary General of the Ministry of Agriculture Number B-5928/PL.210/A/12/2018 dated 31 December 2018.